Montalban Livelihood and Community Center - Cunanan, Jose Ibarra C. (College of Architecture, University of the Philippines Diliman, 2018)
The case of rural poverty for the majority of the Filipinos pushed them to migrate from the countryside to the cities, hoping for better economic opportunities and better lives, which led to fast urbanization in cities. As a response by the government, intensive relocation outside Metro Manila were pushed, especially in areas like Montalban. As a promise, the government assured that greener pastures await the urban poor in the relocation sites. However until now, relocations have been far from being livable. Poor access to livelihood, unemployment, lack of LGU's comprehensive livelihood program, low index in social development, disaster vulnerability, deteriorating support to agriculture, unmaximized resources-all these contributed to the worsening conditions of the relocation sites. Overall, this presents a call to uplift the economic condition of the residents, and ultimately fulfill the years-long promise of the government to provide full assistance to the residents, who for a long time, have been suffering with poor living conditions in the relocation site. Through the agenda of livelihood development, community improvement, and knowledge enhancement, this project, rooted on Montalban's environmental and social capital, aims to provide spaces for various livelihood programs--particularly those relating to organic farming and vetiver-- while also providing facilities for community interaction and learning. Montalban Livelihood and Community Center,as a concrete expression of these agenda, now serves as a catalyst to uplift the lives of the locals.